The effect of squad rotation on physical activity at the 2018 World Cup in Russia. Analysis the most exploited players of the 4 best teams - Kolodziejczyk, M.; Chmura, P.; Konefal, M.; Chmura, J.; Rokita, A.; Andrzejewski, M. (Frontiers in Psychology, 2021)
The purpose of this study was to examine how the four best teams in the 2018 Football Men's World Cup rotate by squad and how this impact the physical activity of the teams in consecutive rounds. The study sample consisted of the 31 players of the 4 best teams, who played in every tournament match, except for the third game of the group stage. The analysis included 186 observations and was carried out on the most exploited players (MEP) excluding goalkeepers, who played at least 450 mins (5 full matches) in the tournament. The analysis was conducted using data collected by an advanced motion analysis system known as STATS®. The selected physical activity parameters analyzed included: total distance covered (m/min), distance covered at various intensity ranges (m/min), top speed (km/h), and number of sprints performed. It was found that all four teams in the third match of the group stage have performed the largest number of rotations with most exploited players and introduced the highest number of rested players (7.75 ± 2.06). A significant increase was observed between the second and fourth match in the 0-7 km/h distance covered (37.99 ± 3.19-39.23 ± 3.35 m/min) and the top speed (28.12 ± 2.22-29.21 ± 2.64 km/h)—p < 0.05. Furthermore, MEPs in the knockout stage, used pacing strategies by increasing the amount of low-intensity running to maintain high intensity during the game. From a practical point of view, this investigation shows that squad rotation can be a valuable support to a pacing strategy by players.